Hubungan Pola Makan Dengan Kejadian Dispepsia Pada Remaja di IGD RSU Gmim Kalooran Amurang - Indry Kalangi; Siska Sibua; Grace Watung (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Background: Improving health status, which is a form of public health development, has not been running optimally because there are still various problems found. Non-communicable diseases have recently become a cause of morbidity and mortality in several countries including Indonesia. Changes in lifestyle and changes in diet are still one of the most common causes of digestive disorders, including dyspepsia.Objective: The purpose of the study was to analyze the relationship between diet and the incidence of dyspepsia in teenager in the emergency room of GMIM Kalooran Amurang Hospital. Methods: This study used cross sectional research design which means studying the dynamics of the relationship between the independent variable with the dependent variable. The population taken in this study were all teenager aged 15-18 years who entered the emergency room of GMIM Kalooran Amurang Hospital, totaling 34 respondents. The sample in this study was taken by means of total sampling. data analysis using chi-square test. Results: Based on the results of statistical tests using chi-square obtained Ï-value = 0.035. From the results of the analysis, the OR value = 8.167 means that a good diet has a chance of 8.167 times better to prevent dyspepsia in adolescents.Â Conclusion: The results of statistical tests using chi-square there is a relationship between diet and the incidence of dyspepsia in teenager in the emergency room of GMIM Kalooran Amurang Hospital. Based on the results of this study, it is necessary to conduct counseling or health promotion, especially on diseases that easily occur in teenager related to diet and healthy lifestyle.